Implementing 3D Printer to Produce Parts in Medical Applications - Roger Johnson; Charles Taylor; G. H. Massiha (Institute of Advanced Engineering and Science, 2017)
The purpose of this project is to show the ability of a 3D printer to produce temporary parts, molds, and jigs for industrial applications. In the industry, it is common for any replacement parts to be milled by a CNC machine or a large inventory of replacement parts to be kept on standby. This represents an underutilization of company capital. This is because there should either be a CNC machine delegated to remake the part, while the other machine is down, or have capital dumped into parts that will not be utilized until a part breaks. A 3D printer can create a temporary part that can take the place of the broken one until another, more permanent, one can be produced or ordered. Although, if this was the only thing it would be used for it also would be underutilized and not bringing out its full potential. It can also make jigs in a fraction of the time, and cost in materials, it would take for a CNC machine to mill it from metal. This increases flexibility of the 3D printer and does not leave it underutilized, thus not being capital that is underutilized.